The Influence of Religious Literacy on Students' Moral Intelligence in the Digital Era: A Case Study of SMAN 4 Cimahi - Rahmat Al Fian, Muhammad Iqbal; Rahmat, Munawar; Jenuri, Jenuri (-, 2024)
The development of technology and social changes have resulted in a moral crisis among the younger generation. Islamic religious education, as a means of character education, should serve as the primary foundation for shaping one's moral intelligence. Religious literacy represents an understanding derived from religious education. Without a proper understanding of the teachings of religious beliefs, character education will never have a solid foundation, and inadequate character education will exacerbate the current moral crisis. It is crucial to examine how religious literacy, as a form of religious understanding and the outcome of Islamic religious education, influences students' moral intelligence in the digital era. This study aims to analyze the influence of religious literacy on students' moral intelligence in the digital era at SMAN 4 Cimahi. The study employs a quantitative approach. A sample of 120 respondents, who are students of SMAN 4 Cimahi, was collected. Quantitative data analysis was performed using SPSS version 25. Based on the results of the study, the results of the statistical test showed that the t-value was 2.111 t. table 1.658, then H1 was accepted and H0 was rejected, so it can be concluded that in general, religious literacy has a positive effect on students' moral intelligence.